Evaluation of the Effect of Heart Failure Reversal Therapy (HFRT) on the Anthropometric Obesity Parameters in Patients of Chronic Heart Failure - Sane, Dr. Rohit; Amin, Dr. Gurudatta; Dongre, Dr. Snehal; Mandole, Dr. Rahul (International Journal of Innovative Research in Medical Science, 2019)
Background: Chronic heart failure (CHF) is a common cause of mortality and morbidity. Obesity influences the CHF development and prognosis. This study was conducted to assess effect of Heart failure reversal therapy (HFRT), a combination of panchakarma and allied therapies, on anthropometric parameters in CHF patients. Methodology: This retrospective study was conducted on data of patients who visited Madhavbaug clinics in Maharashtra, India between July-December 2018. Selection was based upon the availability of complete baseline (day 1 of HFRT) and follow-up data (day 30 of HFRT) of CHF patients who were admitted for minimum 5 days for HFRT. Results: Out of 147 patients, 74.15% were males with mean age 59.15+10.28 years. There was statistically significant decrease (p<0.05) in both mean BMI and abdominal girth at day 30 of HFRT. 42 of 147 patients (28.57%) had hypertension (HTN) with CHF, 22 patients (14.97%) had diabetes mellitus (DM) and 61 patients (41.49%) had both HTN and DM. In all these sub-groups, mean BMI and abdominal girth was significantly decreased (p<0.05) at day 30. Strong positive correlation was found between BMI and abdominal girth on day 1 (R=0.9, P<0.05) and day 30 (R=0.83, P<0.05) by Pearson’s correlation. Similar correlation was found between the two parameters in subsets of CHF patients having HTN or DM or both DM and HTN (p<0.05). Conclusion: HFRT decreased BMI and abdominal circumference significantly in CHF patients, irrespective of the presence of HTN or DM. Both the anthropometric parameters correlated strongly in all co-morbidity subsets of CHF patients.